A Modelling Framework for Lightning-Induced Common-Mode Currents in Photovoltaic Modules and Small Arrays - Smit, Herme Charles (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.